Meningkatkan Pemahaman Konsep Matematika pada Anak Usia Dini dengan Metode Demonstrasi di Tk Mukti Tama Kabupaten Bungo - Tambunan, Ade Zainab Fitri Tambunan; Wiseza, Fitria Carli (Institut Agama Islam Yasni Bungo, 2021)
Abstract This study aims to improve and develop the understanding of mathematical concepts with the demonstration method in early childhood group B. This research is a classroom action research. The subjects in this study were group B students of Mukti Tama Kindergarten, Bungo Regency. Data were collected through observation, field notes, interviews, and documentation. The results of this study indicate a significant change in children's learning abilities. Cycle I as many as 12 children or 63.15% and cycle II as many as 17 children or 89.94%. It can be concluded that the use of the demonstration method on the theme of learning the universe, the basic concepts of early childhood mathematics, material counting the number of stars can improve the learning ability of Mukti Tama Kindergarten, Pelepat Ilir District, Bungo Regency.